Shift Workers’ Psychosocial Well-Being and its Association with Physical Activity and Eating Habits among Healthcare Workers in Klang Valley and the Development of Shift Module - Nor Amira Syahira Binti Mohd Azmi (Universiti Sains Islam Malaysia, 2024)
Matric: 3192536 (FPSK)